2014
DOI: 10.1002/jbm.a.35157
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial polyetheretherketone implants immobilized with silver ions based on chelate-bonding ability of inositol phosphate: Processing, material characterization, cytotoxicity, and antibacterial properties

Abstract: We developed a novel antibacterial implant by forming a hydroxyapatite (HAp) film on polyetheretherketone (PEEK) substrate, and then immobilizing silver ions (Ag(+) ) on the HAp film based on the chelate-bonding ability of inositol phosphate (IP6). First, the PEEK surface was modified by immersion into concentrated sulfuric acid for 10 min. HAp film was formed on the acid-treated PEEK via the soft-solution process using simulated body fluid (SBF), urea, and urease. After HAp coating, specimens were immersed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
(84 reference statements)
0
31
0
Order By: Relevance
“…While changing surface chemistry and introducing roughness seem to provide synergistic effects for osteogenesis, the creation of pores and sulfur‐containing groups by sulfonation does not have the same effect. Surface‐porous PEEK prepared by sulfonation promoted apatite formation in 1x and 1.5x SBF; however, its acidic surface reduces the pH to about 2 . While apatite formation was desirable for osseointegration, the low pH environment induced toxicity that negatively impacted cell viability, proliferation, and in vivo bone formation .…”
Section: Strategies For Improving Osseointegrationmentioning
confidence: 99%
“…While changing surface chemistry and introducing roughness seem to provide synergistic effects for osteogenesis, the creation of pores and sulfur‐containing groups by sulfonation does not have the same effect. Surface‐porous PEEK prepared by sulfonation promoted apatite formation in 1x and 1.5x SBF; however, its acidic surface reduces the pH to about 2 . While apatite formation was desirable for osseointegration, the low pH environment induced toxicity that negatively impacted cell viability, proliferation, and in vivo bone formation .…”
Section: Strategies For Improving Osseointegrationmentioning
confidence: 99%
“…Stoichiometric amounts of silver nitrate in different concentrations were available in a glass reactor previously washed with sulfochromic solution. Subsequently a NaOH dissolution (0.5 mol/L) was added to the above solutions producing silver monoxide, as shown in Equation (1) [23,24].…”
Section: Synthesis Of Silver Nanoparticles and Coating Of Polyetheretmentioning
confidence: 99%
“…Currently, bacterial growth is the main problem of air purification systems such as heaters, air-conditioning and ventilators that are used indoors [1,2]. Some microorganisms are adhered to and absorbed by the parts of the air purifying systems which return to the environment under operational conditions, spreading pathogenic bacteria not only to humans but also to plants and animals [3].…”
Section: Introductionmentioning
confidence: 99%
“…12,14 Some studies have suggested that PEEK materials are relatively resistant to microbial adhesion and hence associated with lower infection rates than their titanium counterparts. 15 Continuously, its minimal radiographic signature allows optimal evaluation of bony fusion on plain radiographs and computed tomography (Figure 2). There is also no risk of metal allergy.…”
Section: Polyetheretherketone Cagesmentioning
confidence: 99%